Assortative preferences for personality and online dating apps: Individuals prefer profiles similar to themselves on agreeableness, openness, and extraversion. (July 2023) - De La Mare, Jessica K.; Lee, Anthony J.
Abstract: Introduction: Established couples tend to have similar personalities (i.e., assortative mating); however, the mechanism for this effect is unclear. Individuals may initially be attracted to others who are like themselves (i.e., have assortative preferences). Alternatively, couples may become more similar over time. These explanations have been difficult to disentangle. Assortative mating may be less common in online situations as barriers related to social homogamy are removed. The current study experimentally investigates which, if any, of the Big Five personality traits were assortatively preferred in an online environment. Methods: Online volunteers and paid participants (205 females and 178 males) viewed 100 ostensible dating profiles comprised of random pairings of facial images and personal descriptions, the latter of which were pre-rated for perceived personality. Participants indicated whether they would like to "match" with each profile, mimicking responses made on dating applications, and completed the Big Five Inventory (BFI-44). Results: Participants showed assortative preferences for agreeableness, openness, and extraversion, but not for conscientiousness or emotional stability. Conclusion: These results suggest that people exhibit assortative preferences in an online dating app environment. If these online preferences translate to long-term relationships, this could help explain similarities found in established couples identified in previous research.